Iterative method for the design of LP0m mode converter. (10th August 2017) - Li, Zebiao; Wang, Qiang; Xu, Shanhui; Yang, Zhongmin; Lin, Honghuan; Huang, Zhihua; Wang, Jianjun; Jing, Feng
Abstract: An iterative method based on coupled mode theory and the steepest descent principle in a microwave waveguide is proposed in the optical waveguide for the design of a LP0m mode converter. After iterative design, a LP02 -LP01 mode converter and a LP03 -LP02 mode converter can achieve 99% conversion efficiency in our model. The 1dB bandwidth of a LP02 -LP01 mode converter is measured as more than 130 nm. These optimum waveguides are simulated by RSoft software and indicate high conversion efficiency as well. Furthermore, we investigate the compatibility of the iterative method for mode converter design with initial waveguides of multiple taper shapes. The proposed method is promising for applications in mode division multiplexing systems.